2022
DOI: 10.1186/s12889-022-14187-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep quality and urolithiasis among general population in Western China: a cross-sectional study

Abstract: Background Growing number of studies have evidently shown that sleep disorders are associated with the recently increased risk of various diseases in general human population. However, the relationship between sleep quality and urolithiasis condition in humans is still unclear. The present study explored the relationship between quality of sleep and urolithiasis in Chinese population of population, western China and hence investigated the effects of sleep quality on urolithiasis disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Grandner et al analyzed more than 700,000 adults from two large cohorts to illustrate that the HTN risk was higher in sleep deficiency compared to 7 h (≤ 4 h: OR=1.86, ≤ 5 h: OR=1.56, ≤ 6 h: OR=1.27, p < 0.0005 for all) (130). A dose-response meta-analysis found a higher HTN risk for shorter sleep duration, and previous meta-analyses reported similar results to strengthen this association (47,131). For OSA patients, the HTN risk was higher than that in healthy controls (OR=2.84, 95% CI: 1.70 to 3.98) and was positively correlated with the OSA grade (132).…”
Section: Hypertensionmentioning
confidence: 78%
See 1 more Smart Citation
“…Grandner et al analyzed more than 700,000 adults from two large cohorts to illustrate that the HTN risk was higher in sleep deficiency compared to 7 h (≤ 4 h: OR=1.86, ≤ 5 h: OR=1.56, ≤ 6 h: OR=1.27, p < 0.0005 for all) (130). A dose-response meta-analysis found a higher HTN risk for shorter sleep duration, and previous meta-analyses reported similar results to strengthen this association (47,131). For OSA patients, the HTN risk was higher than that in healthy controls (OR=2.84, 95% CI: 1.70 to 3.98) and was positively correlated with the OSA grade (132).…”
Section: Hypertensionmentioning
confidence: 78%
“…Another large population-based study obtained similar results, and it estimated the sleep score to assess sleep quality according to a previous study and indicated that a reduced sleep score led to increased KSD risk (hazard ratio [HR] = 1.07, 95% CI: 1.05 to 1.10) ( 45 , 46 ). A prospective study in China measured sleep quality using the Pittsburgh Sleep Quality Index (PSQI) and KSD prevalence, and the PSQI was positively correlated with KSD prevalence (OR=1.18, 95% CI: 1.08 to 1.28) ( 47 ). Another sleep disturbance, obstructive sleep apnea (OSA), is common, with an incidence of 4.0% to 32.8% for middle age and 22.4% for older than 60 years ( 42 ), and has been confirmed to be a risk factor for KSD (HR=1.35, 95% CI: 1.23 to 1.48) ( 48 ).…”
Section: Epidemiological Evidence Of Circadian Rhythm Disruption In Ksdmentioning
confidence: 99%
“…Moreover, initiatives to address the broader socio-economic and cultural factors influencing women's health, such as access to healthcare services, nutritional support, and mental health resources, are critical for mitigating the global impact of FHA and PCOS [68]. Overall, addressing the complex challenges posed by FHA and PCOS requires a comprehensive and integrated approach involving healthcare providers, policymakers, researchers, and advocacy organizations on a global scale [69].…”
Section: Current Statusmentioning
confidence: 99%
“…[ 9 ] Poor sleep quality can lead to decreased immunity and increase the risk of some malignant diseases. Sleep duration, [ 10 ] posture, [ 11 ] and quality [ 12 ] have also been reported to play a vital role in kidney stones. Despite this, previous reports on this subject are sparse, and differ in terms of sleep factors.…”
Section: Introductionmentioning
confidence: 99%